Acute Gaucher Disease-Like Condition in an Indian Infant with a Novel Biallelic Mutation in the Prosaposin Gene - Radha Rama Devi, Akella; Kadali, Srilatha; Radhika, Ananthaneni; Singh, Vineeta; Kumar, M. Aravind; Reddy, Gummadi Maheshwar; Naushad, Shaik Mohammad (Journal of Pediatric Genetics, 2019)
This is the first reported case of prosaposin (PSAP) mutation from India manifesting as an acute neuronal Gaucher disease-like condition. A 2-month-old male baby presented with encephalopathy, resistant tonic–clonic seizures, moderate hepatosplenomegaly, hypotonia, and cherry red spot in the retinae. The child had anemia, thrombocytopenia, elevated chitotriosidase, and normal activity of acid sphingomyelinase and low normal activity of β-glucosidase 1 (β-glucocerebrosidase 1, GBA). The child succumbed in the fourth month of life due to persistent respiratory distress and refractory seizures. The clinical phenotype, cherry red spots, elevated chitotriosidase, and lysosomal assays led to the suspicion of Gaucher disease. Exome sequencing revealed a homozygous stop codon mutation in the PSAP gene (c.G1228T, p.Glu410ter). Prenatal diagnosis in the next pregnancy revealed a carrier fetus, who was unaffected postnatally. The diagnosis of specific activator deficiency such as saposin C and saposin D deficiency (in the current study) should be considered and tested for when Gaucher disease is suspected in an infant with partially deficient or near normal GBA activity.
Keywords: prosaposin; specific activator deficiency; neuronopathic Gaucher disease